Proteinase-activated receptor 2 (PAR2) in hepatic stellate cells – evidence for a role in hepatocellular carcinoma growth in vivo. Issue 1 (December 2016) - Mußbach, Franziska; Ungefroren, Hendrik; Günther, Bernd; Katenkamp, Kathrin; Henklein, Petra; Westermann, Martin; Settmacher, Utz; Lenk, Lennart; Sebens, Susanne; Müller, Jörg; Böhmer, Frank-Dietmar; Kaufmann, Roland
Abstract Background Previous studies have established that proteinase-activated receptor 2 (PAR2 ) promotes migration and invasion of hepatocellular carcinoma (HCC) cells, suggesting a role in HCC progression. Here, we assessed the impact of PAR2 in HCC stromal cells on HCC growth using LX-2 hepatic stellate cells (HSCs) and Hep3B cells as model. Methods PAR2 expression and function in LX-2 cells was analysed by RT-PCR, confocal immunofluorescence, electron microscopy, and [Ca2+ ]i measurements, respectively. The impact of LX-2-expressed PAR2 on tumour growth in vivo was monitored using HCC xenotransplantation experiments inSCID mice, in which HCC-like tumours were induced by coinjection of LX-2 cells and Hep3B cells. To characterise the effects of PAR2 activation in LX-2 cells, various signalling pathways were analysed by immunoblotting and proteome profiler arrays. Results Following verification of functional PAR2 expression in LX-2 cells, in vivo studies showed that these cells promoted tumour growth and angiogenesis of HCC xenografts in mice. These effects were significantly reduced whenF2RL1 (encoding PAR2 ) was downregulated by RNA interference (RNAi). In vitro studies confirmed these results demonstrating RNAi mediated inhibition of PAR2 attenuated Smad2/3 activation in response to TGF-β1 stimulation in LX-2 cells and blocked the pro-mitotic effect of LX-2 derived conditioned medium on Hep3B cells. Furthermore, PAR2 stimulation with trypsin or a PAR2 -selective activating peptide (PAR2 -AP) led to activation of different intracellular signalling pathways, an increased secretion of pro-angiogenic and pro-mitotic factors and proteinases, and an enhanced migration rate across a collagen-coated membrane barrier. SilencingF2RL1 by RNAi or pharmacological inhibition of Src, hepatocyte growth factor receptor (Met), platelet-derived growth factor receptor (PDGFR), p42/p44 mitogen activated protein kinase (MAPK) or matrix-metalloproteinases (MMPs) blocked PAR2 -AP-induced migration. Conclusion PAR2 in HSCs plays a crucial role in promoting HCC growth presumably by mediating migration and secretion of pro-angiogenic and pro-mitotic factors. Therefore, PAR2 in stromal HSCs may have relevance as a therapeutic target of HCC.